Strategies for Realizing Joyful Learning in Islamic Cultural History Education - Beni Suwardi; Rini Susilowati (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study aims to analyze the implementation of learning methods in creating joyful learning within Islamic Cultural History (Sejarah Kebudayaan Islam – SKI) instruction. The research employed a qualitative approach with a case study design. Data were collected through structured observations, semi-structured interviews with teachers and eight selected students, student perception questionnaires using a 5-point Likert scale, and learning documentation. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, supported by source and method triangulation to ensure data validity. The findings reveal that the implemented learning methods encouraged active student engagement, generated positive emotional responses, strengthened reflection on character values, and enhanced students’ ability to connect historical figures and events in Islamic history with their personal experiences. Students’ enthusiasm increased significantly from 48% to 85%, as indicated by observational data. These findings suggest that Islamic Cultural History learning can be developed not merely as a process of historical knowledge transmission but also as a space for character development and spiritual reflection. This approach aligns with the transformative principles of the Merdeka Curriculum and supports the broader goal of providing quality education.